The nutitional importance in the prevention of childhood obesity (Research, Society and Development, 2024)
Childhood obesity has been on the rise in the last three decades, resulting in chronic non-communicable diseases (NCDs). It is essential that there are urgent measures for prevention in the first years of life.  The objective of this research was to identify the most common factors that lead to the increase in childhood obesity, highlighting its causes, diagnoses and treatments.  The study is a bibliographic and integrative review, it is a type of review that aims to provide the synthesis of knowledge presented in scientific studies, where the results can be integrated and applied in practice.  The prevalence of excess weight among Brazilian children has reached alarming figures, around 2 in every 10 Brazilian children, under 5 years old and around 3 in 10, aged between 5 and 9 years old, were overweight in 2019. Foods such as ultra-processed foods are easily accessible, being the villains like fast foods and others, obesity is a risk factor and can progress to morbid obesity, going far beyond childhood.